Synthesis and Characterization of Nano-Composites of Polypropylene / Cr2O3 Nanoparticles Using Licorice Extract - Abdul-Zahra, Mohammed Abdulwahid; Abbass, Nada M. (Iraqi Journal of Science, 2024)
In this work, biosynthesized nanoparticles (Cr2O3) NPs were extracted by licorice root and proven by AFM technique to have a particle diameter of 14.99 nm. These particles were superimposed on polypropylene, and nanocomposites were synthesizes and diagnosed using different techniques, such as FT-IR, SEM, EDS, XRD, TG, DTA, and DSC. To identify the shapes, sizes, and nature of the particles of nanocomposites synthesized in an environmentally friendly way using the mentioned techniques, inhibitory actions of microorganisms were studied using several types of bacteria and fungi. To identify the protective role of environmentally friendly nanoparticles, the antimicrobial activity of the synthesized nanoparticles was characterized by green methods. Antioxidant activity was calculated by DPPH, and acceptable results were obtained for scavenging free radicals.